EFEK KONFIGURASI BAFFLE PADA HEAT EXCHANGER TYPE SHELL AND TUBE SEBAGAI PEMANAS BAHAN BAKAR BIODIESEL B20 - Josua Huwae; Barokah Barokah; Marinus Tappy; Jefta Ratela; Fahriadi Pakaya; Maful Suranto; Baihaqi Baihaqi (Politeknik Kelautan dan Perikanan Bitung, 2022)
B20 is a fuel that is widely used for combustion systems in diesel engines, especially in Indonesia. Apart from having the advantages, biodiesel B20 also has various disadvantages that affect the performance of diesel engines such as those that have a higher flash point than diesel so that biodiesel is more difficult to burn and has a high viscosity which causes less good atomization of fuel and eventually causes deposits in combustion chamber. One or the solution to the problem is that it can be done carefully. The aim of this research is to make a Shell and Tube Heat Exchanger (STHE) by including the insulation in it to improve the heat exchange performance. The method applied in this research is an experiment by testing the performance of the heat exchanger using a cooling water jacket. Some of the equipment used is a diesel engine from the Mitsubishi Diesel Engine, Type 4d35, 4 cylinder, 75 HP. Data were collected at a constant rotation of 1500 rpm at no load. The results showed that the higher the cooling water temperature of the jacket, the higher the biodiesel temperature. With a cooling water jacket temperature of 83oC, it can heat biodiesel at 74.8oC. Keywords : B20 Fuel Oil; Diesel Engine; Heater; Heat Recovery; Jacket Cooler